Fast Food Consumption, Quality of Diet, and Obesity among Isfahanian Adolescent Girls - Mohammad Hossein Rouhani; Maryam Mirseifinezhad; Nasrin Omrani; Ahmad Esmaillzadeh; Leila Azadbakht (Journal of Obesity)
Background and Objective. Few data are available linking fast food intake to diet quality in developing countries. This study was conducted to determine the association between fast food consumption and diet quality as well as obesity among Isfahani girls. Methods. This cross-sectional study was done among 140 Iranian adolescents selected by the use of systematic cluster random sampling. Dietary intakes were assessed using a validated food frequency questionnaire. Diet quality was defined based on energy density and nutrient adequacy ratios (NARs). Results. Individuals in the highest quartile of fast food intake had significantly lower NARs for vitamin B1 (P=0.008), phosphorus (P=0.0250), selenium (P<0.001) and vitamin B2 (P=0.012) compared with those in the lowest quartile. Those in top quartile of fast food intake consumed more energy-dense diets than those in the bottom quartile (P=0.022). High intakes of fast foods were significantly associated with overweight (top quartile: 40% versus bottom quartile: 0%, P=0.0001) and obesity (11.4% versus 2.9%, P=0.0001). Conclusion. Fast food consumption is associated with poor diet quality and high prevalence of overweight and obesity among Isfahani adolescents. Prospective data are required to confirm these findings.